Advancements in Design Research 11 PhD theses on Design as we do in POLIMI - Rampino, Lucia (Design International - Open access, 2019)
"In October 1998, on the occasion of the first conference on design education, Richard Buchanan, then Director of The School of Design at Carnegie Mellon University, envisioned doctoral education in Design as a ""neoteric enterprise"", aimed at finding novel ways of addressing the new problems, ""thereby creating a new body of learning and knowledge"". Twenty years after, these words can still be shared: the new problems affecting our globalised, bewildered and worried society are growing in numbers and in complexity, and novel ways of sorting them out are more sought-after than ever. The present book is part of a series that, since 2017, documents the production of the Politecnico di Milano Design Programme, presenting a summary of the doctoral theses defended each year. Eleven essays are here gathered into four sections: Design Education; Collaborative Processes; Cultural and Creative Companies; Technology for Social Change. In the variety of the researched topics, a common trait can be found in the continuous need of updated ways of addressing complex problems. It is such need that drives the evolving boundaries of design research forward, not just within our Doctoral Programme, but within all the national and international Doctoral Programmes in Design we are acquainted with."